1998
DOI: 10.1007/s002990050373
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from encapsulated somatic embryos of Carica papaya L.

Abstract: Carica papaya L. (papaya) single somatic embryos (2.0 mm diameter) produced in a high-frequency liquid production system were encapsulated in two different synthetic encapsulation compounds. The frequency of regeneration from encapsulated embryos was significantly affected by (1) the concentration of sodium alginate, (2) the presence or absence of nutrient salts in the capsule, and (3) the duration of exposure to calcium chloride. A 2.5% sodium alginate concentration in a half-strength MS salts base resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 16 publications
4
38
1
6
Order By: Relevance
“…The reason for such differences in response may be due to greater mitotic activity in shoot tips than in lateral buds, which are subjected to apical dominance (Verma et al 2010). Recently, micropropagation through encapsulated shoot tips has also been reported in several economically important plants (Singh et al 2006a;b;Faisal and Anis 2007;Rai et al 2008a;Ray and Bhattacharya 2008;Verma et al 2010). Critical evaluation of concentrations of sodium alginate and calcium chloride which affects the gel matrix and capsule quality is one of the important aspects for the successful propagation of plants through encapsulation technology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for such differences in response may be due to greater mitotic activity in shoot tips than in lateral buds, which are subjected to apical dominance (Verma et al 2010). Recently, micropropagation through encapsulated shoot tips has also been reported in several economically important plants (Singh et al 2006a;b;Faisal and Anis 2007;Rai et al 2008a;Ray and Bhattacharya 2008;Verma et al 2010). Critical evaluation of concentrations of sodium alginate and calcium chloride which affects the gel matrix and capsule quality is one of the important aspects for the successful propagation of plants through encapsulation technology.…”
Section: Resultsmentioning
confidence: 99%
“…Successful cases of synthetic seed production and plantlet regeneration have been reported for a wide range of plants including cereals, vegetables, fruits, ornamentals, medicinal plants and forest trees (Redenbaugh et al 1991;Castillo et al 1998;Ara et al 2000;Mandal et al 2000;Rai et al 2009). In most cases somatic embryos have been used in the encapsulation process, however, in recent years adequate efforts have also been made to explore the possibility of encapsulating non-embryogenic, in vitro-derived vegetative propagules such as axillary buds, shoot tips or nodal segments for synthetic seed production (Mathur et al 1989;Ganapathi et al 1992;Sharma et al 1994;Ara et al 2000;Mandal et al 2000;Rout et al 2001;Chand and Singh 2004;Naik and Chand 2006;Singh et al 2006aSingh et al , b, 2009Singh et al , 2010Faisal and Anis 2007;Micheli et al 2007;Rai et al 2008a, b;Lata et al 2009;Sundararaj et al 2010;Verma et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mathur et al (1989) reported that the use of this technology economized upon the medium, space and time requirements. Successful cases of synthetic seeds production and plantlet regeneration have been reported for cereals, vegetables, fruits, ornamentals, aromatic grass and conifers (Fowke et al, 1994;Piccioni and Standardi, 1995;Castillo et al, 1998;Ganapathi et al, 2001;Brischia et al, 2002;Hao and Deng, 2003). However, in most cases somatic embryos were used in the encapsulation process.…”
Section: Introductionmentioning
confidence: 99%
“…The endosperm of artificial seeds could be similar to the endosperm of seeds, but can also be manipulated so as to control growth and reduce the difficulties of the germination of somatic embryos [53,60,81]. While Saiprasad [8] mentioned that usually 3% sodium with complexing solution containing 75 mM Ca 2 Cl 2 ·2H 2 O for half an hour mixing duration provides the optimal structure for artificial seed bead formation, Ara et al [6] indicated that generally 2% sodium alginate gel upon complexation with 100 mM CaCl2·2H2O is the best.…”
Section: Artificial Endosperm Structure and Their Effects In The Artimentioning
confidence: 99%